Reduction of Pharyngocutaneous Fistulae in Laryngectomy Patients by a Comprehensive Performance Improvement Intervention. (30th October 2015) - Li, Ryan J.; Zhou, Xian Chong; Fakhry, Carole; Negrin, Juan; Lee, Gregory; Ha, Patrick; Blanco, Ray; Saunders, John; Califano, Joseph A.
Abstract : Objective: Pharyngocutaneous fistula is a common complication in laryngectomy patients, particularly in previously irradiated cases. We initiated a comprehensive performance improvement intervention in all head and neck surgery patients intended to reduce postoperative infection and fistulae rates. We report our review of outcomes within laryngectomy patients. Study Design: Case series with chart review. Setting: Academic tertiary referral center. Subjects: Nineteen laryngectomy patients at risk of postoperative fistula formation. Methods: We reviewed the medical records of all patients who had undergone laryngectomy procedures between January 2013 and April 2014. Clinicodemographic data were obtained, including history of diabetes, prior radiation therapy, type of reconstruction performed for closure of the pharyngeal defect, and the presence or absence of postoperative fistula. Results: The study population comprised 19 laryngectomy patients. Prior to implementation of our performance improvement intervention, 8 of 11 (73%) patients undergoing laryngectomy developed postoperative fistulae. After intervention, 0 of 8 patients developed fistulae ( P =. 002). Prior radiation, diabetes mellitus, and overall stage were not associated with a reduction in fistula rate ( P >. 05). Conclusion: Comprehensive uniform application of a standard antibiotic prophylaxis, surgical technique, perioperative care, and treatment of comorbid conditions can significantly reduce and potentially eliminate fistulae in laryngectomy patients who are especially at risk.